End-of-life care in COVID-19: An audit of pharmacological management in hospital inpatients. (October 2020) - Jackson, Timothy; Hobson, Katie; Clare, Hannah; Weegmann, Daniel; Moloughney, Catherine; McManus, Sally
Background: Hospital clinicians have had to rapidly develop expertise in managing the clinical manifestations of COVID-19 including symptoms common at the end of life, such as breathlessness and agitation. There is limited evidence exploring whether end-of-life symptom control in this group requires new or adapted guidance. Aim: To review whether prescribing for symptom control in patients dying with COVID-19 adhered to existing local guidance or whether there was deviation which may represent a need for revised guidance or specialist support in particular patient groups. Design/setting: A retrospective review of the electronic patient record of 61 hospital inpatients referred to the specialist palliative care team with swab-confirmed COVID-19 who subsequently died over a 1-month period. Intubated patients were excluded. Results: In all, 83% (40/48) of patients were prescribed opioids at a starting dose consistent with existing local guidelines. In seven of eight patients where higher doses were prescribed, this was on specialist palliative care team advice. Mean total opioid dose required in the last 24 h of life was 14 mg morphine subcutaneous equivalent, and mean total midazolam dose was 9.5 mg. For three patients in whom non-invasive ventilation was in place higher doses were used. Conclusion: Prescription of end-of-life symptom control drugs for COVID-19 fell within the existing guidance when supported by specialist palliative care advice. While some patients may require increased doses, routine prescription of higher starting opioid and benzodiazepine doses beyond existing local guidance was not observed.